KAJIAN TEO-SEKSUAL LONTAR RAHASYA SANGGAMA - Kadek Agus Wardana; I Ketut Donder; I Gede Suwantana (Pangkaja: Jurnal Agama Hindu, 2021)
Sex is an inseparable part of human life. Even so, sex has not been fully understood because more people view sex as something sacred and secret so that sex is only interpreted as a taboo or prohibition to be taught. That is the way of the past view of sex, but lately many parties view sex education is important. Because it is very warmly discussed later. During this time sexuality is often understood as something taboo to talk about especially if it is associated with religion. Of course there are many who refuse to discuss porn in a religious context. Hinduism provides a different view of sexuality. In Hinduism sexuality is seen as a sacred thing in human life because it is implicitly contained in the purusārtha chess teachings, namely dharma, artha, kama, and moksa. One of the goals of human life is the fulfillment of lust or desire (kama) which encourages people to do something that makes people excited in this life. Sex which is equated with kama in Sanskrit and Old Javanese has a place in human life. It cannot be eliminated just behind the current time, because it continues to flow as an instrument of strength to obtain the highest virtue. "People without kama will never want artha and people without kama will never want dharma either. Enjoying spirituality in sexuality activities for Hindus especially Hindus in Bali and Indonesia can be found in the Rahasya Sanggama lontar text. The Balinese have had the Rahasya Sanggama ejection as a sacred guideline in sexual activity, if the guideline is implemented properly, then there should be very few sexual cases in the Balinese environment.